2022
DOI: 10.3389/fpubh.2022.830477
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of the Thermostatic Amplification of Ribonucleic Acid in Bronchoalveolar Lavage Fluid in Smear-Negative Pulmonary Tuberculosis

Abstract: ObjectiveThis study aimed to determine the value of the simultaneous amplification and testing for Mycobacterium tuberculosis in bronchoalveolar lavage fluid (BALF) in the diagnosis of smear-negative pulmonary tuberculosis (PTB).MethodsA total of 316 patients were selected, of which 197 had smear-negative PTB (observation group), and 119 did not have TB (control group). Bronchoscopy was performed in both groups, and BALF samples were collected for acid-fast bacilli smears, simultaneous amplification/testing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…BALF is the most common used respiratory sample type for the diagnosis of PTB besides sputum, which is also preferred by clinicians due to its closer proximity to the lesion. Multiple studies have reported the capability of different molecular tests to diagnose PTB in BALFs, such as Xpert MTB/RIF assay, SAT-TB, LAMP, next-generation metagenome sequencing, nanopore sequencing, etc., with sensitivities raging from 45.18-94.4% [21][22][23][24][25][26] . The comparatively lower results of the Xpert MTB/RIF assay in our study than those previously studies may be related to several factors, including study site, sample source, and the operator, suggesting that we need to improve the level of testing within our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…BALF is the most common used respiratory sample type for the diagnosis of PTB besides sputum, which is also preferred by clinicians due to its closer proximity to the lesion. Multiple studies have reported the capability of different molecular tests to diagnose PTB in BALFs, such as Xpert MTB/RIF assay, SAT-TB, LAMP, next-generation metagenome sequencing, nanopore sequencing, etc., with sensitivities raging from 45.18-94.4% [21][22][23][24][25][26] . The comparatively lower results of the Xpert MTB/RIF assay in our study than those previously studies may be related to several factors, including study site, sample source, and the operator, suggesting that we need to improve the level of testing within our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…8 Consequently, relying solely on MTB culture technique for diagnosing smear-negative PTB may have limited efficacy. 9 The development of molecular diagnostic techniques in recent years has led to significant advancements in the rapid diagnosis of infectious diseases, including TB. 10,11 Xpert MTB/RIF is the most widely used molecular test for rapid diagnosis of TB recommended by the World Health Organization, also in China.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Smear-negative pulmonary tuberculosis is defined by the absence of detectable bacteria in sputum smears, despite clinical and radiological indications of pulmonary TB. 3 The limited bacterial presence in SNPT complicates diagnosis using conventional techniques, resulting in delays in treatment initiation and heightened risk of disease transmission. 4 Given these challenges, the investigation of alternative diagnostic biomarkers is crucial in addressing the diagnostic limitations associated with SNPT.…”
mentioning
confidence: 99%